2021
DOI: 10.1177/17448069211035217
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sex steroids and bladder pain sensitivity in dysmenorrhea

Abstract: Although elevated estradiol levels facilitate chronic pelvic pain in animal models, it remains to be determined whether sex steroid levels are altered in a cross-section of women with chronic pelvic pain (CPP) and those at-risk for developing CPP. We sought to determine if sex steroid levels are increased in women with menstrual pain and whether those changes were more extreme in two groups of women with worsened pelvic pain profiles: a) dysmenorrhea plus evidence of bladder pain sensitivity and b) bladder pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Increased heart rate and changes in heart rate variability are also related to chronic primary pain conditions like IC (54). Dudarev et al (227), recently reported a positive predictive relationship between increased sleep heart rate and next-day pain intensity in patients with two chronic primary pain conditions, fibromyalgia (228) and primary back pain (229), with no interaction between the types of chronic pain.…”
Section: Biological Factorsmentioning
confidence: 99%
“…Increased heart rate and changes in heart rate variability are also related to chronic primary pain conditions like IC (54). Dudarev et al (227), recently reported a positive predictive relationship between increased sleep heart rate and next-day pain intensity in patients with two chronic primary pain conditions, fibromyalgia (228) and primary back pain (229), with no interaction between the types of chronic pain.…”
Section: Biological Factorsmentioning
confidence: 99%
“…The group of Hsieh JC mainly focused on the neuroimaging studies of dysmenorrhea, especially on structural alterations in the brain, BDNF Val66Met Polymorphism, and functional connectivity of pain modulatory systems; 1,[17][18][19][20][21][22][23][24][25][26][27][28][29] the group of Hellman KM mainly focused on the research of bladder pain sensitivity and spontaneous pain in dysmenorrhea women. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] Dawood MY is the most dominant author and the most frequently cited author, which is a medical doctor of the Department of Obstetrics and Gynecology, West Virginia University School of Medicine, writing a great number of reviews on dysmenorrhea, mainly about the nonsteroidal anti-inflammatory drugs like Ibuprofen. 5,[44][45][46][47][48][49][50][51][52][53][54][55][56][57] The team notes that once primary dysmenorrhea is diagnosed, the most effective treatments are NSAID and oral contraceptives.…”
mentioning
confidence: 99%